Recommended Practices and Benchmark Activity for Hydrogen and Oxygen Electrocatalysis in Water Splitting and Fuel Cells - Wei,C; Rao,RR; Peng,J; Huang,B; Stephens,IEL; Risch,M; Xu,ZJ; Shao-Horn,Y (Advanced Materials, 2019)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim Electrochemical energy storage by making H 2 an energy carrier from water splitting relies on four elementary reactions, i.e., the hydrogen evolution reaction (HER), hydrogen oxidation reaction (HOR), oxygen evolution reaction (OER), and oxygen reduction reaction (ORR). Herein, the central objective is to recommend systematic protocols for activity measurements of these four reactions and benchmark activities for comparison, which is critical to facilitate the research and development of catalysts with high activity and stability. Details for the electrochemical cell setup, measurements, and data analysis used to quantify the kinetics of the HER, HOR, OER, and ORR in acidic and basic solutions are provided, and examples of state-of-the-art specific and mass activity of catalysts to date are given. First, the experimental setup is discussed to provide common guidelines for these reactions, including the cell design, reference electrode selection, counter electrode concerns, and working electrode preparation. Second, experimental protocols, including data collection and processing such as ohmic- and background-correction and catalyst surface area estimation, and practice for testing and comparing different classes of catalysts are recommended. Lastly, the specific and mass activity activities of some state-of-the-art catalysts are benchmarked to facilitate the comparison of catalyst activity for these four reactions across different laboratories.